THE EFFECT OF ENGLISH KAMPONG ON SOCIETY SOCIAL-CULTURAL LIFE IN PARE-KEDIRI- EAST JAVA - Putut Handoko; Cahyaningsih Pujimahanani (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2017)
. English kampong is a community who lives and communicates in English situated in Pelem and Tulungrejo Villages, Pare,Kediri, East Java. The establihments and  the increase of English kampong cause the effect on society  social-cultural life.The aim of this research is to find out the effect of English Kampong on society social-cultural life in Pelem and Tulungrejo villages.The theory used is theory of social and cultural change and the method applied is a qualitative research and method of data collecting is an interview and a questionnaire. The finding shows that the society experiences social and cultural change. The people’s value of togertherness, community service and obedience are descreasing.The care of qualification and the importance of education for their children and the society motivation to maintain local tradition are still high. The society are optimistic, pragmatic and materialistic. They tend to live individually and their participation to social activities is decreasing. The tradition of cleaning up the village and tradition relating to religion run well, and the economic tradition changes to be trader or enterpreneur. The infrastrcuture  and residential quality are good and the usage of technology for supporting life is maximum. Society does not place religion aspect as the only intention of life.